2020
DOI: 10.3389/fpls.2020.00781
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Aleurone Peroxidases in Kernels of Insect-Resistant Maize (Zea mays L.; Pob84-C3R) After Mechanical and Insect Damage

Abstract: Peroxidases (PODs) have many biological functions during the plant life cycle. In maize kernels, endosperm PODs have been identified as biochemical contributors to resistance against Sitophilus zeamais, but their identities have not been determined. In this study, we identified these PODs and determined whether their contributions are basal or inducible. Semi-purification and LC-MS/MS analyses showed that the protein ZmPrx35 is the predominant soluble endosperm POD from kernels of Pob84-C3R. Subsequent time-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The POD activity was measured using the method of López‐Castillo et al. (2020) with some modifications. The POD activity was determined by monitoring the formation of tetra guaiacol from guaiacol in the presence of H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The POD activity was measured using the method of López‐Castillo et al. (2020) with some modifications. The POD activity was determined by monitoring the formation of tetra guaiacol from guaiacol in the presence of H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Series of defense mechanisms in response to environmental cues operate within an organism necessary for its survival [57], and specific proteins in response to stress per se are produced in huge quantities through a variety of mechanisms [58]. In our study, proteins associated with LT stress tolerance found in higher abundance include the farnesylated protein, auxin response factor 12, the role of which has been highlighted in case of stressed tomato [59] and banana [60]; IND1 (ironsulfur protein required for NADH dehydrogenase)-like reported earlier in abiotic stress response in rice [61]; Tetratricopeptide repeat (TPR)-like superfamily protein expressed under osmotic stress responses in Arabidopsis [62]; NHL domain-containing protein, the overexpression of which provides resistance to biotic stress in soyabean [42]; Aquaporin PIP2-1 having a full-fledged role in abiotic stress tolerance in plants [63]; and Peroxidase 2-like conferring insect resistance in maize kernels [64]. The present study provides additional evidence that all these proteins contribute to LT tolerance in maize, hence, our findings provide a potent genetic resource for enhancing LT tolerance in this demanding crop plant.…”
Section: Proteins In Relation To 'Response To Stimuli' Under Lt Stres...mentioning
confidence: 97%